Evaluation and ranking of solutions to overcome the barriers of Industry 4.0 enabled sustainable food supply chain adoption - Swapnil Lahane; Vishal Paliwal; Ravi Kant (Cleaner Logistics and Supply Chain)
The food industry plays a significant role in the economy and GDP despite having many obstacles like food safety, food security, demand, and supply gaps. In contrast, the food supply chain has numerous challenges, like food traceability, transportation, and packaging. Industry 4.0 can significantly overcome these challenges in sustainable food supply chain using technologies like IoT, Block chain, cyber security, etc. In India, most food industries are failed to implement Industry 4.0 due to various barriers. This study aims to discover these critical barriers to enable sustainable food supply chain to adopt Industry 4.0 and provide adequate solutions. Using the Pythagorean fuzzy analytic hierarchy process (PF-AHP) and Pythagorean fuzzy-evaluation based on distance from average solution (PF-EDAS) methodologies, we have provided a hybrid framework for the study to prioritize the solutions to overcome the barriers of Industry 4.0 enabled sustainable food supply chain. The relative weights of each barrier are determined using the PF-AHP technique, and the solution to these barriers is prioritized using the PF-EDAS method. The case study of Indian food industry is considered to demonstrate the applicability of proposed framework. The finding of this research reveals that barriers based on ‘organizational’, ‘strategic’, and ‘social’ aspects has encumbers the adoption of Industry 4.0 enabled food supply chain and its negative influence is about more than 50 % on efficient implementation of Industry 4.0 enabled food supply chain. The top management's poor perception of digitization and lack of willingness to adopt Industry 4.0 enabled sustainable food supply chain are the most critical barriers, whereas top management commitment and support is the most vital solution followed by the government to provide the financial subsidies and taxation relief. This study will aid the company and industrial practitioners in developing strategies for efficiently implementing Industry 4.0 in food supply chain for attaining the sustainability. This study outcomes acts as stepping stone and helps to excel the various missions of government of India in regards to Swachh Bharat Abhiyan and Clean Digital India.